2019
DOI: 10.1111/pbr.12690
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing embryo age and media for enhancing hybrid seedling recovery in sour orange (Citrus aurantium) × Sacaton citrumelo (C. paradisi × Poncirus trifoliata) crosses through embryo rescue

Abstract: In citrus, development of new hybrids is difficult due to failure of the germination of zygotic embryos. Hence, this study was conducted to standardize embryo age and media for maximizing the germination and subsequent seedling growth in sour orange × Sacaton citrumelo crosses followed by the identification of simple sequence repeats (SSR) markers for distinguishing the hybrids. A factorial experiment in complete randomized design was conducted with two each embryo age (110–120 and 130–140 days after pollinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Diluted samples were stored at 4 °C for immediate use, while the original concentrates were kept for long-term storage at −20 °C. SSR analysis A set of 37 SSR primers (Soni et al 2019;Tan et al 2007;Ruiz et al 2000) with lengths of 20 or more bp were selected based on the polymorphism information content (PIC) observed in previous studies.…”
Section: Induction Of Embryo Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diluted samples were stored at 4 °C for immediate use, while the original concentrates were kept for long-term storage at −20 °C. SSR analysis A set of 37 SSR primers (Soni et al 2019;Tan et al 2007;Ruiz et al 2000) with lengths of 20 or more bp were selected based on the polymorphism information content (PIC) observed in previous studies.…”
Section: Induction Of Embryo Germinationmentioning
confidence: 99%
“…Previously, it was advocated that the sucrose concentration and medium strength impacted the growth and development of the aerial parts, as well as the plantlet root system in the culture of immature Citrus spp. embryos (Soni et al 2019;Pasqual et al 2003;Pérez-Tornero & Porras 2008).…”
Section: Growth Of Plantletsmentioning
confidence: 99%
“…Various studies reported that the addition of 0.01 mg l -1 GA3 (Riberio et al, 2000;Chagas et al, 2005); 0.1 mg l -1 GA3 (Pasqual et al, 1990;Jumin and Nito, 1996;Singh et al, 2020); 1.0 mg l -1 GA3 (Ollitrault et al, 2007;Zhang et al, 2013;Kurt and Ülger, 2014); 1.5 mg l -1 GA3 (Perez- Tornero and Porras, 2008;Soni et al, 2019) and 2.0 mg l -1 GA3 (Gmitter et al, 1990;Turgutoğlu et al, 2015) in growing media for embryos developing of citrus is to be appropriated. Rangan et al (1969) studied nuceller embryos developing in common sour orange.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that nuceller embryos developing were not seen in growing seeds in 120 days after anthesis. It was determined depending on the examined species and varieties of citrus that 50 days (Wang et al, 1999); 80 days (Tan et al, 2007); 85 days (Xie et al, 2019); 95 days (Singh et al, 2020); 100 days (Tusa et al, 1996;Deng et al, 1996), 105 days (Scarano et al, 2005;Ferrante et al, 2010), 118 days (Chagas et al, 2005); 120 days (Perez-Tornero et al, 2011;Kurt and Ülger, 2019); 130-140 days (Soni et al, 2019) and 135-150 days (Perez-Tornero and Porras, 2008) after pollination was found to be suitable for embryo rescue.…”
Section: Introductionmentioning
confidence: 99%
“…The SSR markers are important for rapid assessment of hybrid, more polymorphic, co-dominant and easily reproducible. Recently, Soni et al (2019) have reported three SSR markers (TAA45, CAC15 and CAC39) to be polymorphic between female and male parents of sour orange and Sacaton citrumelo, showing ability to identify their hybrids. Hence, available user-friendly molecular markers need to be selected for early identification of hybrids of Rangpur lime × sour orange crosses.…”
mentioning
confidence: 99%